N-type polymer semiconductors incorporating heteroannulated benzothiadiazole. Issue 4 (4th January 2023) - Hu, Xiantao; Basu, Aniruddha; Rimmele, Martina; Marsh, Adam V.; Aniés, Filip; He, Qiao; Anthopoulos, Thomas D.; Heeney, Martin
Abstract : A series of four n-type semiconducting copolymers containing a 2, 1, 3-benzothiadiazole (BT) based acceptor annulated with a 2-(1, 3-dithiol-2-ylidene)malonitrile group are synthesized and their optoelectronic properties investigated. Abstract : We report four novel n-type polymer semiconductors containing a 2, 1, 3-benzothiadiazole (BT) based acceptor annulated with a 2-(1, 3-dithiol-2-ylidene)malonitrile (DTYM) group. Four copolymers with varying electron donor groups are investigated with regards to optoelectronic properties. Theoretical calculations and optical characterization indicate that the introduction of the DTYM group leads to backbone twisting and blue-shifted absorption in comparison to the unsubstituted BT analogues, but increases the dipole moment and electron affinity. All polymers exhibit n-type semiconducting character in organic field-effect transistors (OFETs) fabricated by blade coating, with the co-polymer containing a fluorinated bithiophene donor demonstrating the best performance. This work highlights the influence of the DTYM group on polymer semiconductors and further demonstrates its potential as a functional group to enhance electron affinity.